The Opportunities of an Irish Primary School to Utilise a Per Cent for Art, Contemporary Artwork in Reforming Looking and Responding Practice - Sheehan, Dawn (Marino Institute of Education, 2020)
The Primary School Visual Art Curriculum asserts that providing equal opportunities to facilitate looking and responding to art and making art, is vital to the implementation of a balanced visual art education (National Council for Curriculum and Assessment [NCCA], 1999b). Research indicates that this balance does not exist within classroom practice, to the point that Looking and Responding [LAR] is ineffectively implemented. My study investigates: the opportunities of an Irish primary school to utilise a contemporary artwork in reforming LAR practice; the factors contributing to current LAR practice; the influence such practice has on children’s experiences and perceptions of art; and factors that influence LAR reformation. Although considered to be centrally positioned within Irish education, visual art education has been transposed due to literacy and numeracy governance (Granville, 2012). Arts-in-education initiatives serve to realign visual art within children’s education and lives as a whole; however, it is apparent that a disparity exists between policy aspirations and classroom reality (Bamford, 2012). Current curricular reform in which critical skills development is paramount (NCCA, 2020) coincides with attempts to bridge the dichotomy between contemporary art practice and school art practice (Granville, 2012) with the introduction of public art into educational settings. Data was acquired from six children and six teachers during focus group interviews, while my reflexive journal provided insight into my role as teacher-researcher. Descriptive thematic analysis was employed to analyse the data. Findings suggest that low teacher self-efficacy, and a curriculum structure focusing on literacy and numeracy has influenced teachers’ LAR practice. Significantly, the Critical Thinking and Art Talk framework- developed as part of the research intervention- acts as a significant linchpin from which teachers can facilitate child-centred discussions, leading to social constructivist meaning making and critical thinking skills development.